Left-Ventricular 3-D Motion from Tagged MR Images - Abraam Shawki Ibrahim Soliman (2010)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2010 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: Informatics-IFM; Dissertation, Academic